STRATEGI KELEMBAGAAN DALAM KOMPETISI PARIWISATA: PEMBELAJARAN DARI DESA PENTINGSARI - Adi Sucipto (Prodi Administrasi Negara FISIPOL Universitas Kutai Kartanegara, 2019)
Desa Wisata Pentingsari (Dewi Peri) is one of the villages in Indonesia that successfully marked the rise of village actors who wanted to act collaboratively with other parties to improve the welfare of the village community. This study aims to look at the institutional strategy of Dewi Peri in an institutional context. This research method used a descriptive-qualitative approach. The results of the study showed that there had been efforts taken by the actor of Dewi Peri to develop the internal Dewi Peri, including in marketing strategies, improving the quality of human resources and the management system. Whereas in response to external structures, the actor Dewi Peri was performed improvements in infrastructure, homestay and services standardization, and created new attractions as manifestations of innovation.Â Keywords: Strategies, Institutional,Tourism